Investigation of Hilbert–Huang Transform and Fourier Transform for Horizontal-to-Vertical Spectral Ratio Analysis: Understanding the Shallow Structure in Mataram City, Lombok, Indonesia - Harsuko, Mochammad Randy Caesario; Zulfakriza, Zulfakriza; Nugraha, Andri Dian; Sarjan, Achmad Fajar Narotama; Widiyantoro, Sri; Rosalia, Shindy; Puspito, Nanang T.; Sahara, David P. (Frontiers in Earth Science, 2020)
Because of its robustness and practicality, the Horizontal-to-Vertical Spectral Ratio (HVSR) method has been widely used to obtain subsurface structure, mainly the sediment thickness that resides over bedrock. The method uses Fourier Transform to obtain frequency spectrum and calculate the H/V ratio. However, the conventional Fourier Transform method has some limitations; e.g., the inability to remove local noises that are very common in microtremor recordings. In this study, we investigate a relatively new technique, the Hilbert-Huang Transform, in obtaining the HVSR curve, and compare it to the conventional method in terms of its effectiveness in removing local noise through the inversion results of HVSR curves. We used data from a microtremor survey in Mataram City, Lombok Island, Indonesia which experienced a series of destructive earthquakes in 2018. The results show that the S-wave velocity structure derived from the inversion process of the newly-introduced method is in better agreement with the previous study of Mataram City than the conventional method. Furthermore, the resulting S-wave velocity structure is also interpreted based on geological reference, giving new insights into the subsurface structure beneath Mataram City.